MENINGKATKAN MOTIVASI BELAJAR BINA DIRI MENGGOSOK GIGI MELALUI FILM PADA ANAK TUNAGRAHITA SEDANG KELAS I C1 SLB YPAC SUMBAR PADANG - Riry Andria (Universitas Negeri Padang, 2015)
Abstract: This research is motivated by the problems that arise in the field that first class C1 retarded children in SLB YPAC West Sumatra Padang, the lack of motivation in learning brushing teeth. Under these conditions, this study aims to prove effective in increasing the motivation of children's films in tooth brushing for retarded children whose classes I YPAC SLB C1 Padang in West Sumatra.This study uses ABA design with a single subject research methods (SSR). Target behavior in this study is the motivation brushing teeth. These results indicate that the films are less effective in increasing motivation tooth brushing for children with intellectual challenges become. Conditions baseline (A) five times observation, intervention condition (B) 6 times observation. At the inter-state analysis of the number of variables analyzed one variable, with the rate of change in the condition B / A 0%. Overlaps percentage on the initial conditions (A) with the condition of intervention 0%. Therefore it is proven that the working hypothesis ( Ha ) is accepted, so the null hypothesis ( Ho ) is rejected. It can be concluded that the film is effective in increasing motivation brushing teeth . Key word: Film, motivation learning self help to brushing their teet,; intellectual disorder